Developments in electronic engine management and driveline controls : SP-609 (Society of Automotive Engineers, 1985)
Toyota´s new single-chip microcomputer based engine and transmission control system - C.E.M.-The Alfa Romeo engine management system. Design concepts. Trends for the future - A simple engine model for idle speed control - High integration microcontroller yields total vechicle communication solution - A new low pressure single point gasoline injection system - Soot formation in a multipoint-fuel-njected spark-ignited engine - The bendix DEKA fuel injector series. Design and performance - Optimum control logic for manual transmission - Knock control of gasoline engines. A comparison of solutions and tendencies, with special reference to future european emission legislation.